MODELING OF SEISMO-ELECTROMAGNETIC PHENOMENA - Gershenzon N.; Bambakidis G. (My University, 2001)
A model for seismo-electromagnetic (SEM) phenomena is described. The electromagnetic signals generated by mechanical disturbances in the earth's crust have been calculated and compared with reported seismo-electromagnetic signals (SEMS). The major known SEM phenomena, namely, tectonomagnetic variations, electrotelluric anomalies, geomagnetic variations in the ultra-low frequency range and electromagnetic emission in the radio frequency range, have been considered. We have calculated the spectral densities associated with various types of sources. The set of formulas necessary to calculate the detected (filtered and averaged) electric and magnetic fields generated by mechanical disturbances for a wide range of frequencies and at various distances from the source are presented. Based on these formulas, we discuss the conditions under which electrokinetic, piezomagnetic and piezolectric effects could be responsible for SEMS. A comparison of estimated values of SEMS with reported field measurements leads to the conclusion that the sources of most anomalous SEMS are relatively close to the detector. In other words, the source of the signal is local, although the source of the mechanical disturbance which activates it, i.e. the epicenter of an earthquake, may be far away. Recommendations for field experiments (appropriate detector sitting, detector parameters and frequency range) following from the model developed here are presented.
Keywords: SEISMO-ELECTROMAGNETIC PHENOMENA; GEOMAGNETIC VARIATIONS; NUMERICAL SIMULATION